Microfluidic concentration and separation of circulating tumor cell clusters from large blood volumes. Issue 3 (14th January 2020) - Edd, Jon F.; Mishra, Avanish; Dubash, Taronish D.; Herrera, Stefan; Mohammad, Ridhwan; Williams, E. Kendall; Hong, Xin; Mutlu, Baris R.; Walsh, John R.; Machado de Carvalho, Fernanda; Aldikacti, Berent; Nieman, Linda T.; et al.
Abstract : Rare CTC clusters can be purified intact from large blood volumes with a continuous three-stage non-equilibrium inertial separation array (NISA). Abstract : Circulating tumor cells (CTCs) are extremely rare in the blood, yet they account for metastasis. Notably, it was reported that CTC clusters (CTCCs) can be 50–100 times more metastatic than single CTCs, making them particularly salient as a liquid biopsy target. Yet they can split apart and are even rarer, complicating their recovery. Isolation by filtration risks loss when clusters squeeze through filter pores over time, and release of captured clusters can be difficult. Deterministic lateral displacement is continuous but requires channels not much larger than clusters, leading to clogging. Spiral inertial focusing requires large blood dilution factors (or lysis). Here, we report a microfluidic chip that continuously isolates untouched CTC clusters from large volumes of minimally (or undiluted) whole blood. An array of 100 μm-wide channels first concentrates clusters in the blood, and then a similar array transfers them into a small volume of buffer. The microscope-slide-sized PDMS device isolates individually-spiked CTC clusters from >30 mL per hour of whole blood with 80% efficiency into enumeration (fluorescence imaging), and on-chip yield approaches 100% (high speed video). Median blood cell removal (in base-10 logs) is 4.2 for leukocytes, 5.5 for red blood cells, and 4.9 for platelets, leaving less than 0.01% of leukocytes alongside CTC clusters in the product. We also demonstrate that cluster configurations are preserved. Gentle, high throughput concentration and separation of circulating tumor cell clusters from large blood volumes will enable cluster-specific diagnostics and speed the generation of patient-specific CTC cluster lines.